Virtual reality as a non-medical tool in the treatment of anxiety, pain, and perception of time in children in the maintenance phase of acute lymphoblastic leukemia treatment - Liliana Velasco-Hidalgo; Alejandro González-Garay; Blanca Angélica Segura-Pacheco; Ana Luisa Esparza-Silva; Miguel Enrique Cuéllar Mendoza; Miguel Enrique Cuéllar Mendoza; Cecilia Ochoa-Drucker; Sofía Campos-Ugalde; Luis Eduardo Bernabé-Gaspar; Marta Zapata-Tarrés (Frontiers in Oncology, 2024)
IntroductionManagement of pediatric cancer patients involves invasive procedures such as punctures, injections, catheter placements, and chemotherapy which can generate fatigue, nausea, vomiting, anxiety, and pain. Virtual Reality (VR) is a nonpharmacological intervention classified as a cognitive-behavioral method to relieve symptoms.MethodsWe designed a crossover protocol and included 20 patients between 9 and 12 years old; ten were male. All patients had acute lymphoblastic leukemia diagnosis and were treatedwith St. Jude’s XV protocol in the maintenance phase. Pain and anxiety were measured with validated scales in the pediatric population.ResultsAlthough we used a small group of patients, we found statistical difference in the reduction of anxiety and perception of time.DiscussionThese results open a window to non-pharmacological treatments and show a strategy to improve quality of life in children inside the hospital.